Effect of protocol manipulation for determining maximal aerobic power on a treadmill and cycle ergometer: A brief review. - Julio, U. F.; Panissa, V. L. G.; Shiroma, S. A.; Franchini, E. (Strength and Conditioning Journal, 2017)
The development of aerobic fitness is considered important for health and performance. In this sense, evaluation of maximal aerobic power (map) becomes relevant, not only to classify aerobic fitness, but also to obtain important indices related to monitoring and prescription of exercise, especially high-intensity intermittent exercise. However, in the literature, there are a variety of protocols that manipulate different variables, such as initial load, stage duration, increment load, and increments based on rating of perceived effort. Therefore, the aims of the present paper are to analyze studies that manipulate the test protocols and the effects on indices related to map.